2004
DOI: 10.1074/jbc.m408409200
|View full text |Cite
|
Sign up to set email alerts
|

Unique Residues on the H2A.Z Containing Nucleosome Surface Are Important for Xenopus laevis Development

Abstract: Critical to vertebrate development is a complex program of events that establishes specialized tissues and organs from a single fertilized cell. Transitions in chromatin architecture, through alterations in its composition and modification markings, characterize early development. A variant of the H2A core histone, H2A.Z, is essential for development of both Drosophila and mice. We recently showed that H2A.Z is required for proper chromosome segregation. Whether H2A.Z has additional specific functions during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 43 publications
(38 reference statements)
3
62
0
1
Order By: Relevance
“…In mice, H2A.Zdeficient embryos develop normally until implantation (Faast et al, 2001). In Xenopus, the incorporation of H2A.Z into chromatin is not observed until gastrulation (Ridgway et al, 2004). In our study, we found that H2A.Z was re-expressed at detectable levels from the late blastocyst stage when differentiation takes place.…”
Section: Developmentsupporting
confidence: 61%
“…In mice, H2A.Zdeficient embryos develop normally until implantation (Faast et al, 2001). In Xenopus, the incorporation of H2A.Z into chromatin is not observed until gastrulation (Ridgway et al, 2004). In our study, we found that H2A.Z was re-expressed at detectable levels from the late blastocyst stage when differentiation takes place.…”
Section: Developmentsupporting
confidence: 61%
“…46 Moreover in yeast, the deletion of either the Gal4 or Pho4 activators did not influence the ability of H2A.Z to be enriched at model target genes of these respective activators (Lemieux K and Gaudreau L, unpublished data). 47 Conversely, in human cells, results obtained by our and other laboratories suggest that targeting of H2A.Z, by virtue of the p400 or SRCAP such as Tetrahymena thermophila, 15 Xenopus laevis, 16,17 Drosophila melanogaster 18,19 and mice, 20 suggesting that it may provide distinct functions among different organisms. In budding yeast, loss of H2A.Z leads to defects in transcriptional activation, alterations in transcriptional silencing, and increased chromosome loss.…”
Section: H2az and Dna Methylationmentioning
confidence: 91%
“…Intriguingly, a genome-wide survey of Htz1 occupancy in yeast revealed a correlation between Htz1 and four transcription factors, one of which was the Fox homolog Fkh1 [5]. In Xenopus, endogenous H2A.Z is highly expressed in the notochord [50], a tissue that depends on the pha-4 orthologue FoxA2 for establishment [51][52][53]. These observations suggest that certain transcription factors, including forkhead proteins, may be acutely dependent on H2A.Z.…”
Section: Roles For Mys-1 Ssl-1 and Htz-1mentioning
confidence: 92%